Netzmaterial und Selektivität in der Ostseedorschfischerei - Dahm, Erdmann (2003)
Since some time fishing gear scientists express their concern over an observed tendency of the commercial fishery to proceed from codend netting yarns of 3 to 4 mm to higher values or to switch to the use of double instead of single yarn. A recent large EU-financed project collected statistical evidence on the detrimental effect of such behaviour on the selectivity of the codends. In this context data on cod are very scarce. German-Polish experiments in the Baltic from 1999 to 2001 aimed at filling this gap. The investigations prove a clear evidence of a negativ ecorrelation between netting yarn diameter and selectivity factor and/or L50. In addition they demonstrate a clear negative effect on selectivity when switching from single to double yarn The effects are of an order of magnitude that counteracting effects as catch size are masked and support the decision of the IBSFC to define maximum yarn diameters both for single and double yarn netting. A measuring instrument for the enforcement of these new regulations was introduced right in time. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery Research in 2010.